Does PD-1 blockade play a decisive role in the pathological complete remission of unresectable MSS, BRAF V600E-mutated metastatic colorectal cancer: A case report - Tan, Li; Li, Qing-Shu; Peng, Dong; Cheng, Yong (Frontiers in Oncology, 2023)
Background Colorectal cancer (CRC) ranks the third highest incidence among human cancers. With the continuous development of anti-cancer drugs, CRC patients are treated more and more effectively. However, the treatment of patients with unresectable mCRC remains a core point for surgeons worldwide, especially for those with microsatellite stability (MSS) and BRAF V600E mutation, who has been reported to have the worst prognosis. Case Description We report a case of pathological complete remission (PCR) in a patient with unresectable MSS, BRAF V600E-mutated metastatic rectal cancer after using Vemurafenib, Cetuximab in combination with Camrelizumab. Conclusions This case suggested that Vemurafenib, Cetuximab combined with Camrelizumab was effective to MSS, BRAF V600E-mutated mCRC. To benefit more patients, further studies need to be completed.